2005
DOI: 10.1152/ajpcell.00581.2004
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of occludin expression leads to diverse phenotypic alterations in epithelial cells

Abstract: The function of occludin (Occ) in the tight junction is undefined. To gain insight into its role in epithelial cell biology, occludin levels in Madin-Darby canine kidney II cells were suppressed by stably expressing short interfering RNA. Suppression of occludin was associated with a decrease in claudins-1 and -7 and an increase in claudins-3 and -4. Claudin-2 levels were unaffected. The tight junction "fence" function was not impaired in suppressed Occ (Occ-) clones, as determined by BODIPY-sphingomyelin diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
230
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(258 citation statements)
references
References 48 publications
23
230
4
1
Order By: Relevance
“…We first confirmed the previously published behavior of occludin KD cells and compared the results with tricellulin knockdown cells generated in our laboratory. Consistent with previously published results (Yu et al, 2005) we found that KD of Ocln in MDCK cell monolayers does not alter the levels (Fig. 3A) or localization (Fig.…”
Section: Overexpression Of Occludin Increases Physiologic Responses Tsupporting
confidence: 93%
See 1 more Smart Citation
“…We first confirmed the previously published behavior of occludin KD cells and compared the results with tricellulin knockdown cells generated in our laboratory. Consistent with previously published results (Yu et al, 2005) we found that KD of Ocln in MDCK cell monolayers does not alter the levels (Fig. 3A) or localization (Fig.…”
Section: Overexpression Of Occludin Increases Physiologic Responses Tsupporting
confidence: 93%
“…Occludin itself was shown to be a component of a detergent-resistant membrane microdomain (Nusrat et al, 2000;Lambert et al, 2005;Lynch et al, 2007) and several studies have implicated the importance of a cholesterol-rich membrane domain in tight junction function. For example, removal of cholesterol from wild-type MDCK cells results in decreased transepithelial electrical resistance (TER), but has no effect on TER in occludindepleted MDCK cells (Yu et al, 2005). In addition, occludin has also been demonstrated in co-immunoprecipitation experiments to interact with the cholesterol-binding protein caveolin-1 (Nusrat et al, 2000;Lynch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, Yu et al (29) showed that knockdown of occludin did not affect lipid compartmentalization. Thus, the role of occludin in the barrier formation has remained controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, occludin and JAM-A do not form tight junction fibrils when expressed in fibroblasts that lack tight junctions (32,54). Neither paracellular permeability nor tight junction morphology is significantly affected by occludin knockout in mice (87) or knockdown in cell lines (117). Tricellulin is confined mostly to the vertically oriented tight junction strands of tricellular contacts (49).…”
Section: Integral Membrane Proteins Of the Tight Junctionmentioning
confidence: 98%